Morphological Characterization of Ten Genotipes of Large Chili (Capsicum Annuum L). - Lagiman, Lagiman; Supriyanta, Bambang (RSF Conference Series: Engineering and Technology, 2022)
Chili (Capsicum annuum L.) is one of the horticultural commodities that have high economic value which is used as vegetables or cooking spices, industrial raw materials, and has export opportunities. The development of superior chili varieties requires a large variety of germplasm that can be used as parents to be crossed with each other to obtain new superior traits. One of the efforts to determine the diversity of plants is to characterize the morphology and production. The purpose of this study was to obtain distinguishing characters among ten genotypes of large chilies, to determine the value of genetic parameter estimators for several genotypes of large chilies and to identify important characters that influence the yield of large chili genotypes. The study was a single factor field experiment in the form of 10 large chili genotypes arranged in a Completely Randomized Block Design (RCBD) with 3 blocks as replication. Genotypes of large chili are: Arimbi, Baja, Beautiful, Dewa Rengku, Gada, Jayadi, Jenio, Simpatik, Panex, and Thunder. Observation variables included morphological characters (plant habit, leaf color, leaf position, leaf shape, flower position, anther color, pistil color, leaf edge, fruit color), growth variables (plant height, stem diameter, number of leaves), and yield variable (weight per fruit, fruit length, fruit weight per plant). The results showed that all morphological characters for all varieties were the same, namely having an upright habitus, pointed leaf shape, green leaf color, leaf position falling, flower position lowering, purple anther warrant and green pistil stalk warrant, and red fruit skin color.